Polycystic Ovary Syndrome (Pcos) - Kodirova Nargizakhon Umarovna (Zien Journals, 2023)
Polycystic ovary syndrome (PCOS) - fairly common disease which is one of the most relevant problems in gynecological endocrinology. IN review article presents modern data on the etiology, pathogenesis of PCOS. Given rationale for the frequent combination of hyperandrogen and insulin resistance in PCOS. Also characteristic clinical manifestations of PCOS and modern approaches to diagnostics and treatment, including drugs rats of neurotransmitter action (sibutramin, orlistat), drugs of the insulinsensitizers - metformin, progestogens or low-dose single-phase COCs with progesterone 3-generation tagens, synthetic anti-esstrogens - clostilbegit, and other drugs funds. Perspectives are being considered and methods of surgical intervention and tactics for infertility against the background of PCOS
Keywords: PCOS; infertility; sibutramine